BIOLOGICAL DEGRADATION OF BAMBOO PAPER BY TWO WHITE-ROT FUNGAL SPECIES - Novitri Hastuti; Luciasih Agustini; Erlina Nurul Aini; Dian Anggraini Indrawan; Gustan Pari; Heru Satrio Wibisono (Indonesian Journal of Forestry Research, 2023)
Non-wood paper production, such as bamboo paper, is an alternative to meet the massive demand for paper consumption in the recent era. Bamboo paper, made from Bambusa vulgaris fibers and manufactured with the addition of activated nano-carbon, shows an improvement in paper quality. However, there is a potential worry with the incorporation of activated carbon since it may hinder the degradation process of paper. Concerning the substance's life cycle, degradation assisted by the fungal decomposer of this new product is crucial. This study investigated the effects of the white-rot fungi, viz. Phlebiopsis sp and Pycnoporus sp., on the degradation of bamboo paper with- or without- activated nano-carbon (BPAC and BPNAC). In vitro experiments that combined two variables (Fungal agents and Paper types) were carried out for 12 weeks. The results revealed that Pycnoporus sp. was more effective in decomposing both BPAC and BPNAC rather than Phlebiopsis sp. After being degraded by Phlebiopsis sp. and Pycnoporus sp. for 12 weeks, the remaining mass of BPAC was 64.14% and 48.96%, respectively, while the BPNAC was 69.89% and 38.25%, respectively. The ability of these fungal agents on composite-paper degradation was compared to other similar studies. Further investigation and possible applications were discussed.